2010
DOI: 10.1021/ja907777f
|View full text |Cite
|
Sign up to set email alerts
|

Role of Copper Ion in Regulating Ligand Binding in a Myoglobin-Based Cytochrome c Oxidase Model

Abstract: Cytochrome c oxidase (CcO), the terminal enzyme in the mitochondrial respiratory chain, catalyzes the four-electron reduction of dioxygen to water in a binuclear center comprised of a high-spin heme (heme a3) and a copper atom (CuB) coordinated by three histidine residues. As a minimum model for CcO, a mutant of sperm whale myoglobin, named CuBMb, has been engineered, in which a copper atom is held in the distal heme pocket by the native E7 histidine and two nonnative histidine residues. In this work, the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 53 publications
(152 reference statements)
6
17
0
Order By: Relevance
“…With a 442-nm excitation, the low-frequency region of the RR spectra of the reduced proteins exhibit an intense band between 213 and 214 cm -1 that is assigned to an Fe-His stretching vibration, ν(Fe-N His ), from a heme iron(II) bound to a neutral proximal histidine (Figure 3B). These ν(Fe-N His )s are similar to those reported for wild-type swMb and Cu B Mb with or without Cu I bound ( 17-19 ). Thus, the proximal Fe-His bond strength is not significantly affected by the distal substitutions and metal addition as expected from the crystal structure data reported for these engineered proteins ( 15, 16 ).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…With a 442-nm excitation, the low-frequency region of the RR spectra of the reduced proteins exhibit an intense band between 213 and 214 cm -1 that is assigned to an Fe-His stretching vibration, ν(Fe-N His ), from a heme iron(II) bound to a neutral proximal histidine (Figure 3B). These ν(Fe-N His )s are similar to those reported for wild-type swMb and Cu B Mb with or without Cu I bound ( 17-19 ). Thus, the proximal Fe-His bond strength is not significantly affected by the distal substitutions and metal addition as expected from the crystal structure data reported for these engineered proteins ( 15, 16 ).…”
Section: Resultssupporting
confidence: 84%
“…Isotope-editing with 15 NO of the RR spectra of apo-Fe B Mb 1 (NO) reveals a very weakly enhanced ν(NO) at 1606 cm -1 (Table 1). In the low-frequency RR spectra, a band at 560 cm -1 that downshifts with 15 NO is observed in apo-Fe B Mb 1 (NO) (Figure 5A) and is assigned to an ν(FeNO), as previously reported in wild-type swMb and Cu B Mb ( 19, 23 ). Similar RR data were obtained with apo-Fe B Mb 2 (NO) (Figure S6A in the Supporting Information).…”
Section: Resultssupporting
confidence: 79%
“…The totally symmetric in-plane ring breathing modes of the porphyrin macrocycle present in the HF window, in particular, the ν 2 , ν 3 , and ν 4 modes, are sensitive to the oxidation state, spin state, and the nature of axial ligands of the heme. 18,19 The RR spectrum of the ferric hPGRMC1 confirms that the heme is 5CHS, as indicated by the ν 2 , ν 3 , and ν 4 modes at 1566, 1488, and 1373 cm −1 , respectively. The unusually high relative intensity of the ν 3 mode with respect to the ν 4 mode suggests an oxygen-based proximal ligand, such as a hydroxide or tyrosinate.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
“…Hence, it offers rich information regarding the nature of the axial heme ligands and the conformation of the porphyrin ring and peripheral groups as well as the surrounding protein environment. 18,19,3539 The presence of the γ modes in the spectrum of the ferric hPGRCM1 (top trace), which are typically silent in the spectrum of a planar heme with D 4 h symmetry, indicates that the heme is distorted out of plane. The reduction of the protein from the ferric to ferrous state leads to changes in their relative intensities (such as the reduction in intensity of the γ 10 and γ 12 modes), indicating the alteration in the symmetry type of the heme.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Resonance Raman studies on Cu B Mb indicated that the presence of copper affects the CO and NO binding kinetics [28], and stopped-flow experiments confirmed that a CO ligand first binds to Cu B and then transfers to the heme iron [28]. …”
Section: Cubmb a Myoglobin-based Heme-copper Oxidasementioning
confidence: 99%